Creativity in the education process of logistics students: a case study - Ślaski, Paweł (Creativity Studies, 2024)
The article deals with the issue of creativity and the creative process in the education of students. The key to successful thinking is creative teamwork. The power of “team creativity” lies in cross-inspiration, which is of particular value in the case of interdisciplinary teams. The more the students associated with a project differ personally, the more chance there is for them to come up with creative solutions. The article also presents a case study. It presents an example of a 4-step creative process, using Visual Basic for Applications programming. In teams students solve a task related to the analysis of selected economic measures. In the subsequent stages of the process, they solve the problem set by the lecturer using the so-called “collective mind” ideas. The case study was preceded by an analysis of surveys in which students referred to their knowledge of creative teaching methods and assessed their attractiveness. The literature study conducted analyzed teamwork in the process of student education and the creative process that fosters creative thinking. Two economic metrics were analyzed to determine the product group’s contribution to the company’s profitability and demand profile. Using Microsoft Excel spreadsheet, two procedures using Visual Basic for Applications computer programming were developed and verified in a case study based on quantitative data.